Evolving Understanding of Antarctic Ice‐Sheet Physics and Ambiguity in Probabilistic Sea‐Level Projections. Issue 12 (14th December 2017) - Kopp, Robert E.; DeConto, Robert M.; Bader, Daniel A.; Hay, Carling C.; Horton, Radley M.; Kulp, Scott; Oppenheimer, Michael; Pollard, David; Strauss, Benjamin H.
Abstract: Mechanisms such as ice‐shelf hydrofracturing and ice‐cliff collapse may rapidly increase discharge from marine‐based ice sheets. Here, we link a probabilistic framework for sea‐level projections to a small ensemble of Antarctic ice‐sheet (AIS) simulations incorporating these physical processes to explore their influence on global‐mean sea‐level (GMSL) and relative sea‐level (RSL). We compare the new projections to past results using expert assessment and structured expert elicitation about AIS changes. Under high greenhouse gas emissions (Representative Concentration Pathway [RCP] 8.5), median projected 21st century GMSL rise increases from 79 to 146 cm. Without protective measures, revised median RSL projections would by 2100 submerge land currently home to 153 million people, an increase of 44 million. The use of a physical model, rather than simple parameterizations assuming constant acceleration of ice loss, increases forcing sensitivity: overlap between the central 90% of simulations for 2100 for RCP 8.5 (93–243 cm) and RCP 2.6 (26–98 cm) is minimal. By 2300, the gap between median GMSL estimates for RCP 8.5 and RCP 2.6 reaches >10 m, with median RSL projections for RCP 8.5 jeopardizing land now occupied by 950 million people (versus 167 million for RCP 2.6). The minimal correlation between the contribution of AIS to GMSL by 2050 and that in 2100 and beyond implies current sea‐level observations cannot exclude future extreme outcomes. The sensitivity of post‐2050 projections to deeply uncertain physics highlights the need for robust decision and adaptive management frameworks. Plain Language Summary: Recent ice‐sheet modeling papers have introduced new physical mechanisms—specifically the hydrofracturing of ice shelves and the collapse of ice cliffs—that can rapidly increase ice‐sheet mass loss from a marine‐based ice‐sheet, as exists in much of Antarctica. This paper links new Antarctic model results into a sea‐level rise projection framework to examine their influence on global and regional sea‐level rise projections and their associated uncertainties, the potential impact of projected sea‐level rise on areas currently occupied by human populations, and the implications of these projections for the ability to constrain future changes from present observations. Under a high greenhouse gas emission future, these new physical processes increase median projected 21st century GMSL rise from ∼80 to ∼150 cm. Revised median RSL projections for a high‐emissions future would, without protective measures, by 2100 submerge land currently home to more than 153 million people. The use of a physical model indicates that emissions matter more for 21st century sea‐level change than previous projections showed. Moreover, there is little correlation between the contribution of Antarctic to sea‐level rise by 2050 and its contribution in 2100 and beyond, so current sea‐level observations cannot exclude future extreme outcomes. Key Points: Incorporating ice‐shelf hydrofracturing and ice‐cliff collapse mechanisms highlights ambiguity in post‐2050 sea‐level projections These mechanisms make post‐2050 sea level more heavily emissions dependent and can significantly revise high‐emissions projections upwards Current Antarctic retreat is dominated by by different processes than and exhibits little correlation with late‐century changes